'One for all and all for one': Cluster, employment, and the global economic crisis. Evidence from the German mechanical engineering industry1. (30th September 2013) - Wrobel, Martin
Abstract How regional clusters – and the firms constituting it – respond to major economic shocks has only recently become the centre of attention in regional research. Taking the concept of 'adaptive resilience' as a point of departure, and using a mixed methods approach (firm survey, multivariate analysis, expert interviews), this study explores the response of cluster and non‐cluster firms of the German mechanical engineering sector during the initial phase of the crisis (2008–2009). Findings show a significantly more positive employment trend in cluster firms than in non‐cluster firms. Further analyses of the mechanisms that allow cluster firms to exhibit more resilience than other firms suggest that solidarity and altruism among regional actors were of particular importance in the beginning of the crisis.